Two Novel Compounds Isolated from the Marine Fungal Symbiont of Aspergillus unguis Induce Apoptosis and Cell Cycle Arrest in Breast Cancer Cells: In vitro Study - Bashari MH; Agung MUK; Ariyanto EF; Al Muqarrabun LMR; Salsabila S; Chahyadi A; Rosandy AR; Afifah E; Afni M; Atmaja HE; Putri T; Utami F; et al. (Journal of Experimental Pharmacology)
Muhammad Hasan Bashari,1 Mochamad Untung Kurnia Agung,2 Eko Fuji Ariyanto,1 Laode Muhammad Ramadhan Al Muqarrabun,3 Syefira Salsabila,3 Agus Chahyadi,3 Andi Rifki Rosandy,3 Ervi Afifah,4 Merry Afni,5 Harold Eka Atmaja,5 Tenny Putri,5 Fitria Utami,5 Beginer Subhan,6 Syafrizayanti,7 Yosie Andriani,8 Elfahmi3,9 1Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, Indonesia; 2Department of Marine Science, Faculty of Fisheries and Marine Science, Universitas Padjadjaran, Bandung, West Java, Indonesia; 3University Center of Excellence for Nutraceuticals, Bioscience and Biotechnology Research Center, Bandung Institute of Technology, Bandung, West Java, Indonesia; 4Graduate School of Master Program, Faculty of Medicine, Universitas Padjadjaran, Bandung, Indonesia; 5Biomedical Laboratory, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, Indonesia; 6Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, Bogor, West Java, Indonesia; 7Biochemistry Laboratory, Department of Chemistry, Universitas Andalas, Padang, West Sumatera, Indonesia; 8Institute of Climate Adaptation and Marine Biotechnology, Universiti Malaysia Terengganu, Kuala Nerus, Terengganu, Malaysia; 9School of Pharmacy, Bandung Institute of Technology, Bandung, West Java, IndonesiaCorrespondence: Muhammad Hasan Bashari, Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Bandung, 40161, West Java, Indonesia, Email bashari@unpad.ac.id Elfahmi, School of Pharmacy, Bandung Institute of Technology, Bandung, West Java, Indonesia, Email elfahmi@fa.itb.ac.idPurpose: A promising feature of marine sponges is the potential anticancer efficacy of their secondary metabolites. The objective of this study was to explore the anticancer activities of compounds from the fungal symbiont of Aaptos suberitoides on breast cancer cells.Methods: In the present research, Aspergillus unguis, an endophytic fungal strain derived from the marine sponge A. suberitoides was successfully isolated and characterized. Subsequently, ethyl acetate extraction and isolation of chemical constituents produced was performed. The structures of the isolated compounds were identified using several spectroscopic methods, ie, UV, NMR, and mass spectrometry. Thereafter, MDA-MB-231, MCF-7 breast cancer cells and HaCat cells were treated with the isolated compounds. Not only viability, apoptosis, and cell cycle analyses were conducted, but also the mRNA expression of MCL1, BCL2L1, AKT1 and CDK2 were evaluated.Results: The extract showed cytotoxic activity in breast cancer cells. Two novel compounds were successfully isolated and identified, ie, Unguisol A (15.1 mg) and Unguisol B (97.9 mg). Both compounds share the same basic skeleton and comprise an aromatic ring which is attached to a sulphur-containing, seven-membered ring via an oxygen atom. This marked the first-time isolation of Unguisol A and Unguisol B from A. unguis, highlighting their novelty. Both compounds induced early apoptosis (p < 0.01) and cell cycle arrest at the S phase (p < 0.05) in MDA-MB-231 cells, but not in HaCat cells. Both compounds suppressed BCL2L1 and AKT1 mRNA expression (p < 0.01).Conclusion: Two novel compounds were isolated from A. unguis. Unguisol A and Unguisol B induced apoptosis in MDA-MB-231 breast cancer cells via BCL2L1 mRNA downregulation, while both compounds induced cell cycle arrest at the S phase through AKT1 mRNA downregulation. Keywords: Aspergillus unguis, drug screening assays, Porifera, triple negative breast neoplasms